Reassessing the Pediatric Dosing Recommendations for Unfractionated Heparin Using Real-World Data: A Pharmacokinetic-Pharmacodynamic Modeling Approach - Salem, Ahmed M; Niu, Tao; Li, Chao; Moffett, Brady S; Ivaturi, Vijay; Gopalakrishnan, Mathangi (Journal of clinical pharmacology, 2022)
Optimal pediatric dosing of unfractionated heparin (UFH) is challenging because of the paucity of clinical outcome and pharmacokinetic-pharmacodynamic (PK/PD) studies in pediatrics. This study aimed to: (i) develop a PK/PD model for UFH, quantified by anti-factor Xa assay, and the UFH effect, measured by activated partial thromboplastin time (aPTT); and (ii) use simulations to evaluate pediatric UFH infusions for achieving the anti-factor Xa (0.3-0.7 IU/mL) therapeutic target. Electronic health record data were retrospectively collected from 633 patients aged <19 years admitted to Texas Children's Hospital. The PK/PD model was developed using a 70% (training)/30% (testing) split-sample approach. A 1-compartment PK model with linear elimination adequately described the UFH PK. An allometrically scaled body weight on clearance (CL) and volume of distribution (Vd) with an age-dependent maturation function of extracellular water on Vd were the covariates identified. Comparable with literature, the typical values for CL and Vd were 3.28 L/(h·50 kg) and 8.83 L/50 kg, respectively. A linear model adequately described the UFH-aPTT relationship with an estimated slope of 150 seconds/(IU/mL). Simulations of the currently recommended starting infusions (28 IU/h/kg for pediatrics <1 year old or 20 IU/h/kg for pediatrics >1 year old) showed that the anti-factor Xa therapeutic target was achieved only in 15.3%, 14.6%, 36.9%, and 45.11% of subjects in the age groups of <1 year, 1-6 years, 6-12 years, and 12-19 years, respectively. In conclusion, the UFH anti-factor Xa target is not achieved initially, especially in young pediatrics, suggesting the need to optimize UFH dosing to achieve higher therapeutic success.